2017
DOI: 10.1016/j.chembiol.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide Map of Targets of T790M-EGFR-Directed Covalent Inhibitors

Abstract: Summary Patients with non-small cell lung cancer (NSCLC) that have kinase-activating epidermal growth factor receptor (EGFR) mutations are highly responsive to first- and second-generation EGFR inhibitors. However, these patients often relapse due to a secondary, drug-resistant mutation in EGFR where the gatekeeper threonine is converted to methionine (T790M). Several third-generation EGFR inhibitors have been developed that irreversibly inactivate T790M-EGFR while sparing wild-type EGFR, thus reducing epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 58 publications
2
65
0
Order By: Relevance
“…To assess the structural impact of the EGFR G724S mutation on the EGFR kinase we performed structural analysis based on a previously published co-crystal structure of rociletinib bound to EGFR (PDB ID: 5UWD) (Fig. 3a ) 30 . As described before the glycine-rich loop is an essential element for ligand binding and the glycine at position 724 is in direct contact with the adjacent ELREA motif that is subject to deletion mutations in affected patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the structural impact of the EGFR G724S mutation on the EGFR kinase we performed structural analysis based on a previously published co-crystal structure of rociletinib bound to EGFR (PDB ID: 5UWD) (Fig. 3a ) 30 . As described before the glycine-rich loop is an essential element for ligand binding and the glycine at position 724 is in direct contact with the adjacent ELREA motif that is subject to deletion mutations in affected patients.…”
Section: Resultsmentioning
confidence: 99%
“…As described before the glycine-rich loop is an essential element for ligand binding and the glycine at position 724 is in direct contact with the adjacent ELREA motif that is subject to deletion mutations in affected patients. The ELREA sequence plays a crucial role in the alignment of the regulatory helix αC that is a key element in the transition between the active and inactive kinase domain conformations 30 . It is therefore conceivable that the EGFR G724S mutation influences structure and dynamics of the binding site and thereby the affinity toward third-generation EGFR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Dacomitinib is a pan-erythroblastic leukemia viral oncogene homologue (ERBB) inhibitor which targets wildtype and mutant forms of EGFR that possess activating L858R or exon 19 deletion mutations in addition to T790M mutation 42,43 . For the purpose of our study, we utilized the A431 epidermoid cancer cell line as it was previously reported to be characterized by a high expression of wildtype EGFR 44 , and has been utilized in experiments profiling EGFR covalent inhibitors 45,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Derivatisation of ABX‐1431 with an alkyne enrichment handle (ABX‐1431_ABP, Figure B) confirmed CNS penetrance and in vivo target engagement by ABX‐1431 in the mouse brain after a 4 h treatment with a single 25 mg kg −1 oral dose . This general approach has also been used to profile the cysteine‐targeted covalent drugs afatinib (EGFR inhibitor) and ibrutinib (BTK inhibitor), as well as the newly developed third generation EGFR inhibitors osimertinib, PF‐06747775 and rociletinib . Additionally, a dichlorotriazine‐based probe has been utilised recently to label bromodomains on lysine and tyrosine residues, and the high selectivity profile of a lysine‐targeted covalent inhibitor of the lipid kinase PI3Kδ was also determined using similar strategies …”
Section: Target Engagement and Selectivity Profilingmentioning
confidence: 87%